2023
DOI: 10.3390/diagnostics13050964
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on the Application of Cytogenomic Approaches in Chronic Lymphocytic Leukaemia

Abstract: Chronic lymphocytic leukaemia (CLL) is a haematological malignancy characterised by the accumulation of monoclonal mature B lymphocytes (positive for CD5+ and CD23+) in peripheral blood, bone marrow, and lymph nodes. Although CLL is reported to be rare in Asian countries compared to Western countries, the disease course is more aggressive in Asian countries than in their Western counterparts. It has been postulated that this is due to genetic variants between populations. Various cytogenomic methods, either of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 133 publications
0
4
0
Order By: Relevance
“…Cytogenetic analysis is useful for identifying certain chromosomal abnormalities that affect the disease’s prognosis and could affect the choice of treatment [ 33 ]. We observed that 1%, 18%, 4% and 1% of patients, respectively, had 13q14 del, 11q23 del, 17p13 del and trisomy.…”
Section: Discussionmentioning
confidence: 99%
“…Cytogenetic analysis is useful for identifying certain chromosomal abnormalities that affect the disease’s prognosis and could affect the choice of treatment [ 33 ]. We observed that 1%, 18%, 4% and 1% of patients, respectively, had 13q14 del, 11q23 del, 17p13 del and trisomy.…”
Section: Discussionmentioning
confidence: 99%
“…Stable CLL could be considered as a peculiar case of a long-term equilibrium between the clonally transformed B-cell population and immune-mediated antineoplastic activity. For the comparative analysis of CD54 expression on T lymphocytes as well as of HLA-I and APM molecule expression in B and T cells, immune-fluorescence data were expressed as ratio of mean intensity fluorescence (MIF) value for each lymphocyte subset and the control MIF value obtained after staining the same cell population with the isotype control mAb, as described [5,52].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, early stage asymptomatic patients show partial long-term benefits or no therapeutic effect from early drug treatment, while patients with advanced disease necessarily require first-line therapy to limit disease progression [1][2][3]. Several alterations, such as p53 mutation, immunoglobulin heavy-chain variable gene (IGHV) mutational status, cytogenetic and epigenetic modification [4][5][6], as well as micro-environmental stimulation [7], have been proposed as predictive and/or diagnostic biomarkers of the disease. However, the need for additional disease markers is recognised as essential to improve the diagnostic and predictive criteria of CLL disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation